Detailed Photophysical Studies of Poly(9, 9-di-(2-ethylhexyl)-9-H-fluorene-2, 7-vinylene) in Liquid Media and Thin Films. Issue 12 (December 2022) - Khatun, Rijia; Majhi, Koushik; Sinha, Subrata
For the present work, solvent (toluene, o- xylene, chloroform, chlorobenzene, and 1, 2-dichloroethane) and concentration-dependent (∼10 −6 –10 −3 g ml −1 ) photophysical properties of poly(9, 9-di-(2-ethylhexyl)-9-H-fluorene-2, 7-vinylene) (PEFV) were investigated in detail in liquid media as well as thin films. Also, temperature-dependent (3–60 o C) fluorescence emission measurements of PEFV were conducted in liquid media. The steady-state and time-resolved data indicate the existence of weak interchain interaction in liquid media at high concentration. However, both ground-state aggregation and interchain interaction are present for PEFV in thin film. The interchain interaction plays a dominant role on the fluorescence emission of PEFV in thin film on the red side of the spectra. Graphical Abstract